Dynamic characteristics of magnetorheological fluid squeeze flow considering wall slip and inertia. (January 2020) - Zhang, Xinjie; Wu, Ruochen; Guo, Konghui; Zu, Piyong; Ahmadian, Mehdi
Magnetorheological fluid has been investigated intensively nowadays, and magnetorheological fluid shows large force capabilities in squeeze mode with wide application potential such as control valve, engine mounts, and impact dampers. In these applications, magnetorheological fluid is flowing in a dynamic environment due to the transient nature of inputs and system characteristics. Hence, this article undertakes a comprehensive study of magnetorheological fluid squeeze flow dynamics behaviors with wall slip, yield, and inertia. First, the dynamic model with the bi-viscous constitutive of magnetorheological fluid squeeze flow including wall slip and inertial force is presented. Then, the mathematical model is validated, matching magnetorheological fluid squeeze dynamic test results very well. Finally, the dynamics behavior and mechanism of magnetorheological fluid squeeze flow with inertia, yield, and wall slip are explored. Results show that (1) increasing yield stress and decreasing initial gap will increase the magnetorheological fluid vertical force greatly; (2) the wall slip affects the yield surface of magnetorheological fluids in the squeeze zone and affects the squeeze force; (3) the inertial force is increasing tremendously as the increased excitation frequency and yield stress and should be included with high-frequency excitation or yield stress.